Universal dependence on disorder of two-dimensional randomly diluted and random-bond ±J Ising models - Hasenbusch, Martin; Toldin, Francesco Parisen; Pelissetto, Andrea; Vicari, Ettore (Physical review. E, Statistical, nonlinear, and soft matter physics, 2008)
We consider the two-dimensional randomly site diluted Ising model and the random-bond ±J Ising model (also called the Edwards-Anderson model), and study their critical behavior at the paramagnetic-ferromagnetic transition. The critical behavior of thermodynamic quantities can be derived from a set of renormalization-group equations, in which disorder is a marginally irrelevant perturbation at the two-dimensional Ising fixed point. We discuss their solutions, focusing in particular on the universality of the logarithmic corrections arising from the presence of disorder. Then, we present a finite-size scaling analysis of high-statistics Monte Carlo simulations. The numerical results confirm the renormalization-group predictions, and in particular the universality of the logarithmic corrections to the Ising behavior due to quenched dilution.